VD_FINDINFO Jug / 2016 / 397 vom 9. Februar 2015 - VD Tribunal cantonal (2015)
RÉDUCTIONEN GÉNÉRAL, INDEMNITÉEN GÉNÉRAL, AVOCAT, DÉPENS, HONORAIRES | 107 al. 2 LTF, 406 al. 1 let. d CPP (CH), 433 al. 1 CPP(CH)